The Loch Ness monster and other lake mysteries - Jeffrey, Gary (Graphic mysteries, 2006)
Presents three lake mysteries written in graphic novel format including "The Loch Ness Monster," "The Lake Champlain Monster," and "South Bay Bessie," the Lake Erie Monster.